PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN PROFESIONALISME TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - Y. Djoko Suseno, Aris Wibowo & (Universitas Slamet Riyadi, 2017)
The purpose of this study was to analyze the effect of leadership,organizational culture, professionalism and work satisfaction to employeeperformance. The others to knows work satisfaction are moderated effect ofleadership, organizational culture and professionalism to employee performancein the Mental Hospital of Central Java Provincial Government Owned. Thepopulation of as many as 1,382 employees. Samples taken as many as 10% ofthe population with cluster random sampling method so that a sample of 140people.. Analysis techniques used multiple linear regression and test the absolutedifference. The results showed that the leadership have a significant effect onemployee performance. Organizational culture have a significant effect onemployee performance. Professionalism have a significant effect on employeeperformance. Job satisfaction have a significant effect on employee performance.Work satisfaction moderate the effect of leadership on employee performance.Work satisfaction moderate the effect of organizational culture on employeeperformance. Work satisfaction does not moderate the effect of professionalismon employee performance.Keywords: leadership, organization culture, profesionalism, work satisfaction,employee performance